1997
DOI: 10.1103/physrevc.55.2043
|View full text |Cite
|
Sign up to set email alerts
|

Covariant and light-front approaches to theρ-meson electromagnetic form factors

Abstract: The -meson electromagnetic form factors are calculated, both in covariant and light-front frameworks with constituent quarks. The effect of the breakdown of rotational symmetry for the one-body current operator in the null plane is investigated by comparing calculations within light-front and covariant approaches. This allows to choose the appropriate light-front prescription, among the several ones, to best evaluate the -meson form factors. ͓S0556-2813͑97͒02303-0͔

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
288
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 129 publications
(311 citation statements)
references
References 18 publications
20
288
3
Order By: Relevance
“…The violation of the angular condition is a consequence of taking into account only the contribution of the residue of the pole of the spectator particle in the Cauchy integration of the k − momentum, as has also been shown in a recent numerical study in this model [11].…”
mentioning
confidence: 84%
“…The violation of the angular condition is a consequence of taking into account only the contribution of the residue of the pole of the spectator particle in the Cauchy integration of the k − momentum, as has also been shown in a recent numerical study in this model [11].…”
mentioning
confidence: 84%
“…Technically, the use of the Drell-Yan frame (longitudinal momentum transfer q + = q 0 + q 3 = 0) and the projection on to the light-front (performing the integration on the minus momentum component analytically in the Mandelstam formula) simplifies drastically the computation of the form factor. This approach has been applied to the pion [4,5,19], the kaon [20] as well as to the ρ [21].…”
Section: Light-front Constituent Quark Modelmentioning
confidence: 99%
“…Therefore, an analysis with covariant analytical models, can be useful to pin down the main missing features in a truncated light-front Fock-space description of the composite system. In this respect, the rotational symmetry breaking of the plus component of the electromagnetic current, in the Drell-Yan frame, was recently studied within an analytical model for the spin-1 vertex of a composite two-fermion bound state [3,4]. It was shown that, if pair term contributions are ignored in the evaluation of the matrix elements of the electromagnetic current, the covariance of the form factors is lost [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the rotational symmetry breaking of the plus component of the electromagnetic current, in the Drell-Yan frame, was recently studied within an analytical model for the spin-1 vertex of a composite two-fermion bound state [3,4]. It was shown that, if pair term contributions are ignored in the evaluation of the matrix elements of the electromagnetic current, the covariance of the form factors is lost [3,4,5,6]. The complete restoration of covariance in the form factor calculation is found only when pair terms or zero modes contributions to the matrix elements of the current are considered [4,5,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation